TECHNICAL NOTE PRELIMINARY MAPPING OF THE SITES OF MEMORY OF THE ATLANTIC SLAVE TRADE AND THE HISTORY OF ENSLAVED AFRICANS AND THEIR DESCENDANTS IN BRAZIL TECHNICAL TEAM (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
The aim of this technical note is to describe the procedures performed and to indicate the use of the viewer of the Preliminary Thematic Map of Sites of Memory of the Atlantic Slave Trade and the History of Enslaved Africans in Brazil. This map was made based on a survey of one hundred of sites of memory conducted by the LABHOI/UFF, in partnership with the "Slave Route project: Resistance, Liberty, Heritage", UNESCO (2014).